APPRAISAL OF SOME MOSSES FOR BIOMONITORING AIR BORNE HEAVY METALS IN KATHMANDU VALLEY - Shakya, K.; Chettri, M. K.; Sawidis, T (Ecoprint: An International Journal of Ecology, 2004)
Epiphytic mosses were sampled from 35 sites in Kathmandu valley for assessing air borne heavy metals (Cd, Co, Cr, Cu, Mn, Ni, Pb and Zn) through passive monitoring technique. These sampling sites were broadly divided into 3 categories viz., inside, along and outside the ring road. The ring road encircles core part of two cities, Kathmandu and Lalitpur. Among all the studied epiphytic mosses, three species like Brachythecium plumosum (Hedw.) B.S.G; Fabronia matsumurae Besch. and Erythrodontium julaceum (Schwaegr.) Par. were very common and mostly showed high bioaccumulation of these metals. Bioaccumulation ability in these three mosses was further evaluated statistically using paired t- test. Result of paired t-test indicated that Erythrodontium julaceum significantly (P=0.05) have high bioaccumulating capacity of the heavy metals like Cd, Cr, Co, Cu, Pb and Zn than other moss species. Therefore, the epiphytic moss species Erythrodontium julaceum has been recommended as one of the suitable moss species to be considered for future biomonitoring programme. Contamination factor indicated severe contamination of Cd, Cr, and Pb at most sampling sites inside and along the ring road areas. Similarly, it also showed severe contamination of Zn at some areas outside the ring road. Key words: Heavy metals, Mosses, monitoring, contamination factors, Kathmandu. Ecoprint Vol.11(1) 2004.